Theoretical investigation and experimental support for the cavitation bubble dynamics near a spherical particle based on Weiss theorem and Kelvin impulse - Xiaoyu Wang; Guanhao Wu; Xiaoxiao Zheng; Xuan Du; Yuning Zhang; Yuning Zhang (Ultrasonics Sonochemistry, 2022)
In the present paper, the laser-induced cavitation bubble dynamics near a fixed spherical particle is comprehensively investigated based on the Weiss theorem, the Kelvin impulse theory and the high-speed photography experiment. Firstly, the applicability range of the theoretical model in the time and the space is statistically obtained based on sufficient experimental results. Then, the in-depth theoretical analysis is carried out in terms of the liquid flow field and the bubble Kelvin impulse with the corresponding experimental results as the reasonable support. In addition, the theoretical prediction model of the bubble movement is established and experimentally fitted from the analytic expression of the Kelvin impulse. Through our research, it is found that: (1) the applicability range of the Kelvin impulse theory for the bubble near the spherical particle is approximately the dimensionless distance between the bubble and particle (γ) greater than 0.50. (2) The effect of the particle on the liquid velocity between the bubble and the particle is mainly manifested in the form of the image bubble, which always causes the liquid velocity in this region to be significantly lower than other surrounding regions. (3) The average movement velocity of the bubble centroid can be reasonably predicted by establishing a directly proportional function between the Kelvin impulse and the velocity with the relationship constant (α) equal to 3.57×10−6 ± 1.63×10−7 kg.